Manajemen Kualitas Air Di Perairan Umum - Gulo, Florencelin Dwinda (CV. SINAR HOWUHOWU, 2025)
Water quality is a crucial factor affecting ecosystem sustainability and the socio-economic impacts of aquatic resources. This study reviewed academic literature to assess the state of water quality in Indonesia, identify the main causes of pollution such as domestic, industrial and agricultural effluents, and evaluate the effectiveness of existing management. The findings show that a number of water bodies, including the Citarum River and Lake Limboto, have suffered significant quality degradation due to eutrophication and heavy metal pollution. Weak regulations, lack of community involvement, and limited institutions exacerbate this condition. Therefore, collaborative and innovative approaches involving government, communities and the private sector are needed to achieve adaptive and sustainable water management.